(untitled) (Palíndromo, 2018)
This article is about the distinction between extraordinary and ordinary art and the directions that the art evaluation has taken in our post-modernity society. The scope here is the literary art campus, including some relevant questions regarding to visual arts. The principal issue is the judgment of taste and the process that intends to turn the art in something sacred. Pierre Bourdieu is the central author in this study – especially in his books Distinction and The rules of the art– where he approaches questions about the value of art and the artist’s autonomy. Another important point is to wonder about the position of the readers and stu-dents nowadays in relation to these rules. Finally, it is concerned in discussing how art and these rules are connected with any kind of symbolic violence.